Antihypertensive effect of etamicastat in dopamine D2 receptor deficient mice - Armando, Ines (Hypertens Res, 2018)
Abnormalities of the D(2)R gene (DRD2) play a role in the pathogenesis of human essential hypertension; variants of the DRD2 have been reported to be associated with hypertension. Disruption of Drd2 (D(2)(−/−)) in mice increases blood pressure and may cause salt sensitivity. The hypertension of D(2)(−/−) mice has been related, in part, to increased sympathetic activity and renal oxidative stress and endothelin B receptor expression. We tested in D(2)(−/−) mice the effect of etamicastat, a reversible peripheral inhibitor of dopamine-β-hydroxylase that reduces the biosynthesis of norepinephrine from dopamine and decreases sympathetic nerve activity. Blood pressure was measured in anesthetized D(2)(−/−) mice treated with etamicastat by gavage, (10 mg/kg), conscious D(2)(−/−) mice and D(2)(+/+) littermates, with the D(2)R selectively silenced in the kidney, treated with etamiscastat in the drinking water (10 mg/kg/day). Tissue and urinary catecholamines and renal expression of selected G protein-coupled receptors, enzymes related to the production of reactive oxygen species, and sodium transporters were also measured. Etamicastat decreased blood pressure both in anesthetized and conscious D(2)(−/−) mice and mice with renal-selective silencing of D(2)R to levels similar or close to those measured in D(2)(+/+) littermates. Etamicastat decreased cardiac norepinephrine and increased cardiac and urinary dopamine levels in D(2)(−/−) mice. It also normalized the increased renal protein expressions of ETB, NADPH oxidase isoenzymes, NHE3, and NCC, and increased the renal expression of D(1)R but not D(5)R in D(2)(−/−) mice. In conclusion, etamicastat is effective in normalizing the increased blood pressure and some of the abnormal renal biochemical alterations of D(2)(−/−) mice.